Metacognition patterns of the students in solving mathematical problems: Analyzed from adversity quotient and gender - Widiyasari, Ririn (Universitas Islam Raden Intan Lampung, INDONESIA, 2023)
Background: Metacognition significantly influences students' effectiveness in solving mathematical problems. Variability in metacognitive patterns among students is shaped by factors such as adversity quotient (AQ) and gender.Aim: This research aimed to explore metacognitive patterns in mathematical problem-solving among students majoring in mathematics at Universitas Muhammadiyah Jakarta, with a specific focus on differences due to AQ and gender.Method: Adopting a qualitative approach with a phenomenological framework, this study included six students (three males and three females) from the 2021–2022 academic year. These students represented different AQ categories: climber, camper, and quitter. Data collection involved tests, observations, and interviews.Results: The investigation showed that students with a climber AQ, irrespective of gender, adeptly utilized all metacognitive knowledge facets: declarative, procedural, and conditional. In contrast, male campers engaged primarily in declarative and procedural knowledge, while male quitters demonstrated negligible engagement. Female campers predominantly employed declarative knowledge, occasionally integrating conditional knowledge. Female quitters, however, did not exhibit significant usage of metacognitive knowledge. Regarding metacognitive regulation—planning, monitoring, and evaluation—students identified as climbers displayed proficiency across all these aspects, regardless of their gender.Conclusion: The study underscores the influence of AQ and gender on metacognitive patterns in mathematical problem-solving, noting an exception in climbers who consistently exhibit effective metacognition. These insights could guide educational strategies to bolster metacognitive skills in the context of mathematics education.